PENGARUH TEKNIK PEMASAKAN DAN WAKTU TERHADAP KARAKTERISTIK TINGKAT KEMATANGAN TELUR AYAM NEGERI - Muhamad Faras Arhab; Alya Yunita Widyanti; Muhammad Fernanda Alvi Yasin; Nabila Banowati; Veronika Noviaty; Pribadi Mempuni Adhi (Department of Food Technology, Universitas Pasundan, Bandung, 2022)
Eggs are the most consumed source of protein. Everyone has a preference for their egg coocked levels. With different egg cooking techniques, it can produce different egg cooked levels characteristics as well. Therefore, this research was conducted experimentally which aims to determine the cooking technique used by considering the appropriate temperature and cooking time to achieve the desired level of cooked egg. The research data were analyzed using descriptive methods. The cooking techniques used in this study were the egg-boiling technique using the shell, the egg-boiling technique without the shell, and the egg-frying technique. The three cooking techniques used time parameters of 5, 6, 8 and 10 minutes. In the processing of each egg cooking technique, physical conditions are observed and the egg temperature is checked when it reaches that time parameter. In the cooking technique of boiling eggs without the shell and the technique of boiling eggs using the shell, it was observed that the changes in the condition of the egg white and yolk were changed in the form of physical solidification from the effect of temperature and boiling time on the eggs. The results of the third study of egg cooking techniques that were carried out showed that the eggs with the cooking technique of frying eggs reached perfection faster with an egg temperature of 149°C, at 5 to 8 minutes this showed differences in the condition of egg whites and egg yolks, namely starting from solidify and change color. Meanwhile, for eggs carried out with the cooking technique of boiling eggs with shells with a treatment of 5 to 8 minutes at a temperature of 99.3°C, they still have not reached the perfect level of cooked, the perfect level of maturity in eggs is obtained in 10 minutes.